Creatine supplementation: its effects on human muscular performance and body composition - Volek, J. S.; Kraemer, W. J. (The Journal of Strength and Conditioning Research, 1996)
The use of creatine (Cr) in its supplemental form, Cr monohydrate has become rather widespread. The discovery that the Cr and phosphocreatine (PCr) content in human muscle can be increased by oral ingestion of supplemental Cr has led to numerous studies examining its benefits on exercise performance. Creatine monohydrate supplementation appears to result in an increased ability to maintain power output during high-intensity exercise and increase the rate of PCr resynthesis during the recovery phase of intermittent high-intensity exercise. Subjects supplemented with Creatine monohydrate demonstrate a reduction in the accumulation of plasma lactate, ammonia, and hypoxanthine, indicating an alteration in energy metabolism and an attenuation of ATP degradation. Thus, higher concentrations of Cr seem to enhance the muscle's ability to sustain the high ATP turnover rates encountered during strenuous exercise. Another potential benefit is an increase in body mass which results from the ingestion of Creatine monohydrate; however, the composition of the weight gain remains undetermined. This article discusses the theoretical basis for Cr supplementation and reviews what is known about its effects on performance.